Profiling the seasonal variability of decomposition odour from human remains in a temperate Australian environment. Issue 6 (1st November 2020) - Deo, Alisha; Forbes, Shari L.; Stuart, Barbara H.; Ueland, Maiken
ABSTRACT: This project aimed to collect and analyze odour profiles from whole human cadavers across various seasons, to contribute to the understanding of the different volatile organic compounds (VOCs) produced in human decomposition. This research will ultimately enhance our understanding of the key VOCs used by cadaver-detection dogs to locate human remains. VOCs were collected onto sorbent tubes and analyzed using two-dimensional gas chromatography – time-of-flight-mass-spectrometry (GC×GC-TOFMS). Five trials were conducted at the Australian Facility for Taphonomic Experimental Research (AFTER) across various seasons including autumn, winter and spring. Analysis showed differentiation between compounds and compound classes produced by each donor. Cadavers placed during warmer weather showed higher variety and abundances of compounds and cadavers placed during cooler weather showed fewer VOCs with lower abundances. All seasonal trials showed variation, with no consistently recurring compound being identified. Further trials would need to be carried out in order to increase the VOC database, allowing for identification of key VOCs. This may consequently be used by cadaver-detection dogs for locating human remains at any time of the year.